2010
DOI: 10.1093/rpd/ncq522
|View full text |Cite
|
Sign up to set email alerts
|

Cellular burdens and biological effects on tissue level caused by inhaled radon progenies

Abstract: In the case of radon exposure, the spatial distribution of deposited radioactive particles is highly inhomogeneous in the central airways. The object of this research is to investigate the consequences of this heterogeneity regarding cellular burdens in the bronchial epithelium and to study the possible biological effects at tissue level. Applying computational fluid and particle dynamics techniques, the deposition distribution of inhaled radon daughters has been determined in a bronchial airway model for 23 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Alpha radiation releases a large amount of energy in a very short linear track alpha (high-energy transfer capacity, HET), which is more biologically significant than either beta or gamma radiations and reacts much more readily with deoxyribonucleic acid (DNA), generating oxidative stress (reactive oxygen species, ROS) and hydroxyl radical attack through radiolysis, despite their reduced penetrating capability [44][45][46][47].…”
Section: Genomic Effects Of Alpha Radiationmentioning
confidence: 99%
“…Alpha radiation releases a large amount of energy in a very short linear track alpha (high-energy transfer capacity, HET), which is more biologically significant than either beta or gamma radiations and reacts much more readily with deoxyribonucleic acid (DNA), generating oxidative stress (reactive oxygen species, ROS) and hydroxyl radical attack through radiolysis, despite their reduced penetrating capability [44][45][46][47].…”
Section: Genomic Effects Of Alpha Radiationmentioning
confidence: 99%
“…The role of radon and its radioactive decay products as human carcinogens has been established by epidemiologic studies in humans [27]. It is well demonstrated that radon induces DNA mutations and subsequential functional damage [28]. The high-linear energy transfer of α-particles emitted by radon and radon decay products can directly attack genomic DNA and cause mainly double-strand breaks in DNA [29].…”
Section: Toxic Effects Of Exposure To Radon In Humanmentioning
confidence: 99%
“…The heterogeneous aerosol deposition results in heterogeneous spatial activity distribution of inhaled radon progeny in the bronchial airways [3]. Due to the short range of emitted alphaparticles and the relatively short half life of radon progeny, the heterogeneity is reflected in the dose distributions too [4]. Whereas it remains an open question whether the measure of dose heterogeneity increases or decreases the risk, the understanding of the mechanisms leading from radon exposure to lung cancer is not expected if the effects of locally high doses are not studied [5].…”
Section: Introductionmentioning
confidence: 99%